E-CONTRACT UPDATED FORM OF CIVIL AGREEMENT - Slobodska, Iryna; Protsko, Vladyslava (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: consideration of legal support of electronic contracts in Ukraine, research of the current state of use and the procedure for concluding e-contracts. The method of the article is to look at the legal security of electronic contracts in Ukraine, which has now become clearer about the order of laying e-contracts. The methodological basis of the research was laid by the deep scientific and special methods of knowledge: dialectical - for looking at the legal security of agreements in the field of electronic contracts, as a rich process with its own mechanism, which is constantly developing and improving lazy; formally logical - when the current state of legal security is reached, it is related to the provisions of the agreements, which are determined by the understanding of the form of the agreement; structural-functional - to characterize the types of contract forms; system analysis and synthesis - for signing the letter and electronic forms of the contract and establishing a link between them; formal-legal - when clarifying the content rules of law, which regulate the procedure for laying down electronic contracts. The continuum of significant methods has made it possible to assess the legal security of the arrangement of electronic contracts, to reveal the essential deficiencies and to formulate scientific and legal propositions about their adoption. Based on the results of the analysis, we became aware that the current scientific and theoretical field is actively discussing the legal nature of “electronic contracts”. Invariably, there is a tendency to evaluate these agreements as civil-legal (government-legal). The main reason for this is the presence of a legal basis for the arrangement of e-contract, the legal force of these agreements, especially in the context of the new practice of their arrangement in the Internet. The agreement is one of the legal provisions for the regulation of government relations. Part 1 of Art. 67 of the Economic Code of Ukraine, praised by the Verkhovna Rada on September 16, 2003 it is appointed that the partnership with other businesses, organizations, communities in all areas of government activity is established on the basis of agreements, which is important for the establishment of a government agreement. Art. 181 of the Economic Code of Ukraine, the obligatory language of the economic agreement in the letter form was established. To the adoption of the Law of Ukraine "On Electronic Commerce" dated 3 September 2015 acquires urgency of the follow-up of the supply of the electronic form of the contract, which means to simplify the subjects of the state the procedure for laying down the electronic state contracts and to allow them to comply with the norms of legislation in the form of electronic and written forms of the contract.